Enhancement an Algorithm to Hide a Text into a Digital Image as a Steganography Technique - Abd Kadum, Salman; Hameed Abaidah, Tameem (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2017)
In this paper we enhance an algorithm to hide a text into a digital image as steganography technique. This algorithm consists of two major parts, the first, is procedure to hide a text into a digital image, and the second, is procedure to get a hide text from it, further than this algorithm consists of many parts or procedures to enhance this algorithm to complete this process. We use the Least Significant Bit method to hide the message or text, in order to keep the features and characteristics of the original image. By experiment and implement of this algorithm by visual basic 6.0, the algorithm seems work in a butter case by hiding and getting text from a digital image which is used as a carrier of this text, it means that we use two stages in this paper to accomplish it: 1) detecting that steganography has been used, and then 2) by reading the embedded message.